The Essential Role of Pharmacists during the COVID-19 Pandemic: a review article (Journal of Pharmaceutical Negative Results, 2022)
COVID-19 is a pandemic viral infection that caused a hesitated health state for all countries worldwide; being a healthcare professional puts you in crucial responsibilities and drive to be more aware and efficient in managing and controlling this pandemic; the pharmacist has a great role in preventing the COVID-19 from dissemination and providing all healthcare services such as drugs, vaccines, sterilized materials, and sterilization techniques for all healthcare settings, the pharmacist has an essential step in raising the degree of COVID-19 eradication in all countries, in this review, a collection of many articles were reviewed, discussed to conclude that the pharmacist is one of the biggest healthcare professionals. They are working continuously to control this COVID-19 pandemic.